Public Special Education Teachers' Challenges, Social Support, and Meaning in Managing Children on the Autism Spectrum - Diaz, Kristel Anne; Madrigal, Dennis V. (Technium Social Sciences Journal, 2025)
Special Education Teachers are the primary providers of knowledge for children on the autism spectrum. With the increasing number of autism-diagnosed children, all special education teachers are probably going to need to teach a child with autism. Thus, this phenomenological study explored the public special education teachers' experiences in managing children on the autism spectrum in Northern Negros Occidental. Using a purposive sampling method, the data were collected from ten public special education teachers managing children on the autism spectrum in northern part of the province of Negros Occidental through an unstructured in-depth interview. There were only two encompassing questions and probing questions asked to extract significant information. The data were analysed using the modified van Kaam approach, as advocated by Moustakas. The findings of the study indicated that teachers wrestled with various challenges, coped by reinforcing social support, and found sense of meaning in managing children on the autism spectrum. Ultimately, this study underscores the demanding yet meaningful nature of their work, requiring immense patience and adaptability. The results not only underscore the necessity of raising awareness but also emphasizes the urgent need for enhanced institutional and social support to address teacher challenges and suppress attrition in this vital field.